Performance of different dynamic oxygenation indices incorporating heart rate to predict non-invasive ventilation outcomes in hypoxemic respiratory failure - Omnia Mohamed Mamdouh; Ashraf El Sayed Ahmed; Ahmed Zidan Abuzeid Hashem; Hadeer Ahmed Elshahaat (The Egyptian Journal of Bronchology)
Abstract Background Non-invasive ventilation (NIV) becomes crucial ventilatory support for respiratory failure patients, but wasting time in high-risk patients for suspected NIV failure and delayed intubation with invasive mechanical ventilation (IMV) is also fatal. Early prediction of NIV succeeded or failed patients is a potentially effective strategy for minimizing mortality and improving outcomes. This study evaluated the predictive power of dynamic change of hypoxemic indices incorporating heart rate (HR) [ROX-HR and POX-HR] in predicting NIV outcomes in hypoxemic acute respiratory failure (ARF), to get the best benefits of NIV and avoiding delayed intubation and IMV aiming to decrease intensive care unit (ICU) mortality risk. Results This study enrolled 120 patients who were admitted and initiated NIV at Respiratory ICU and Anesthesia and Surgical ICU at Zagazig University Hospitals for ARF from June 2023 to May 2024. Enrolled patients were 80 males and 40 females with mean ± SD of their age 51.5 ± 13.4yrs. 40 (33.3%) had failed NIV and 80 (66.7%) had succeeded with the mean ± SD of NIV duration being 26.4 ± 15.6 h. Several oxygenation indices in the form of ROX, POX, ROX-HR, and POX-HR were measured at different points of time during NIV (baseline, after 2 h, 12 h, and after 24 h). Patients with failed NIV showed a highly statistically significant drop in ROX, POX, ROX-HR, and POX-HR than patients with succeeded NIV. At all measured time points, indices incorporating heart rate (ROX-HR and POX-HR) had better performance in predicting NIV outcomes. POX-HR had the highest accuracy than other measured indices in early prediction (after 2 h) of NIV outcomes. A ROX-HR index of > 5 and a POX-HR index of > 4 were correlated with a low chance of NIV failure at all time points during the first 24 h, even after applying multivariate regression analysis for confounders. Conclusions Heart rate–based indices are more reliable in predicting NIV outcomes. Among the assessed indicators, POX-HR has the highest accuracy in predicting the outcomes of NIV at an early stage.